Kajian Karakteristik dan Persebaran Aktivitas Komersial Di Kawasan Koridor Jalan Seturan, Sleman - Adrian Bani Firdaus; Ragil Haryanto (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Commercial activity on area of Seturan Street actually been around since thelast few years. This activity then being on growth continuously and exhibit somephenomenon. Some appearence that was seen on this area is about location ofcommercial activity. The location of commercial activity are not only on the edge of themain road, but also by other roads and scattered in some locations. Furthermore,commercial activity on the area of Seturan Street also look diverse in terms of goods orservices types offered and also the arrival frequency of consumer. Commercial activitynot only offer goods of daily needs, but also has developed to more complex on a varietyof other needs. Based on these appearence, the purpose of this study was to examine thecharacteristics and dispersion of commercial activity on the area of Seturan Streetcorridor. The method used in this research was descriptive quantitative approach withthe sample used was a commercial building owners or actors/parties running commercialactivities in the building and using stratified random sampling technique or techniqueswith proportional stratified sample of the sample collection.